Noninvasive prenatal testing for fetal trisomy in a mixed risk factors pregnancy population - Wai-Hou Li; Peng-Hui Wang; Chi-Mu Chuang; Yi-Wen Chang; Ming-Jie Yang; Chih-Yao Chen; Kuan-Chong Chao; Ming-Shyen Yen (Elsevier, 2015)
Objective: This study assesses the performance of noninvasive prenatal testing (NIPT) for fetal aneuploidies in a mixed risk factors pregnancy population. Materials and methods: Data review of 169 pregnant women undergoing prenatal aneuploidy screening in a single tertiary medical center was conducted. Indications included maternal anxiety, advanced maternal age, abnormal nuchal translucency, and high/moderate risk of first trimester Down syndrome screening. Multifetal pregnancies and patients receiving in vitro fertilization were also enrolled for analysis. Results: A total of 169 patients were enrolled in this study during a time period from July 2012 to June 2014. For patients' ≥ 34 years, anxiety about amniocentesis was the most common reason for patients selecting NIPT for fetal aneuploidy screening, with 107 (88.4%) patients choosing NIPT for this reason. Among the total patient population, two patients showed a positive result from NIPT. One patient displayed 47, XXY, which was confirmed to be a false-positive result. The other patient displayed trisomy 18, which was confirmed by an amniotic cell culture. The sensitivity for NIPT is 100% with the specificity 99.4%. Conclusions: NIPT for fetal aneuploidy in a mixed risk factors pregnancy population showed high accuracy. NIPT applied to the low risk population might reassure the anxious family.